Pendekatan Metode Bermain III-I Untuk Meningkatkan Kemampuan Mengumpan Pemain Bolavoli Pada Tim Putri Puslatkot Kota Kediri 2021 - Junaidi, *Slamet; Muharram, Nur Ahmad (Ilmu Olahraga, 2021)
Increased sports achievements, can give pride to athletes, coaches, including sports organizations at one level as well as even the country will be raised, if it can give maximum achievement, where the national flag can be flown at world championships. Evaluation can be done in the middle and at the end of the exercise, with the aim of taking corrective action, if there is a process that does not match the goals to be achieved. The evaluation of the ability of the volleyball players for the Puslatkot team was carried out in the form of trials three times, against teams from clubs around the city of Kediri. The research method, which aims to improve the ability to pass/pass over, uses a semi-experimental method, where research subjects in addition to training for this research process, are also carried out during other exercises. This research approach is quantitative, where the data is in the form of numbers at the beginning of the exercise and in the middle of the exercise, with a pretest post-test design. Based on the statistical hypothesis test in the table above, it shows that the value of Sig.2-tailed (p=0.00<0.05), in accordance with the decision-making criteria, it can be concluded that the 3-1 playing practice method affects the ability to pass during volleyball matches for City Puslakot players. Kediri.